On numerical methods for one problem of mixed type - Sytova, S. (Mathematical Modelling and Analysis, 2001)
This article is devoted to further investigation of numerical methods for one differential problem of mixed type. We consider a two‐dimensional first‐order differential equation with one complex‐valued and one real constant coefficients. So, we have an elliptic problem with respect to the first argument and a hyperbolic problem with respect to the second one. The equations of such type are generalized transfer equations. Firstly, the correctness of the problem stated is discussed. Secondly, possible difference scheme of the multicomponent modification of the alternating direction method is proposed. Its stability and convergence is investigated. Results of numerical experiments on modelling of nonlinear regime of surface volume free electron laser are analyzed.Vieno mišruas tipo uždavinio skaitinis sprendimasSantrauka. Straipsnyje tiriami mišraus tipo uždavinių sprendimo algoritmai. Nagrinėjama dvimatė pirmosios eilės diferencialinė lygtis, kurios vienas koeflciantas yra kompleksinė funkcija, o kitas ‐ realaus tipo skaičius. Taigi uždavinys yra elipsinio tipo vieno kintamojo atžvilgiu ir hiperbolinio tipo kito kintamojo atžvilgiu. Ištirtas baigtinių skirtumų schemų stabilumas ir konvergavimas. Schemos realizavimui naudojamas dagiakomponentinis iteracinis metodas, ištirtas jo stabilumas. Pateikti matematinio modeliavimo rezultatai.First Published online: 14 Oct 2010